Drug utilization at the out-patient department of the teaching hospital of jaffna - Layanthini, S.; Nanthakumaran, K.; Guruparan, Y.; Thiyahiny, S.N. (University of Jaffna, 2018)
Rational use of medicines reduces the risk and wastage and increase the benefits to the patients. Drug utilization studies describe pattern of drug use in health facilities which in turn help to optimize the drug use and promote rational use of medicines. Prescription is a valuable tool to get information regarding drug utilization. This study has been designed to describe the drug utilization using drug use indicators at the out patient department (OPD) as preliminary step to optimize the drug use at Teaching Hospital, Jaffna. In this study fourteen drug use indicators were used to determine the drug utilization pattern at OPD of Teaching Hospital Jaffna. They are WHO prescribing indicators: 1) average number of drugs per encounter, 2) percentage of drugs prescribed by generic name, 3) percentage of encounters with an antibiotic, 4) percentage of prescriptions with an injection, 5) percentage of drug prescribed from essential medicines list/ formulary; WHO facility indicators: 6) availability of essential medicines list, 7) availability of key drugs; WHO complementary indicators: 8) percentage of patients treated without drugs, 9) average drug cost per encounter, 10) percentage of drug cost spent on antibiotics, 11) percentage of drug cost spent on injections and indicators developed by investigators: 12) percentage of prescriptions with the documentation of reason for prescribing a drug, 13) percentage of drugs prescribed for common diseases, and 14) percentage of complete prescriptions in terms of dose, dosage form, frequency, duration and route of administration. It is a hospital based cross sectional study and total of 640 prescriptions containing 1834 drugs on a single day were collected and analyzed. Results show that some indicators such as percentage of prescription with injection (2.7%), percentage of drugs prescribed from essential medicine list (95.6%) and percentage of prescriptions with the documentation of reason for prescribing a drug (76.4%) are satisfactory. However, important prescription indicators are unsatisfactory particularly percentage of drugs prescribed by generic name (41.4%), encounters with an antibiotics (71.9%) and completeness of prescription (0.0%). The study concludes that overall prescribing practice is unsatisfactory and indicates the urgent need of adequate training for prescribers and developing monitoring system for prescribing and use of antibiotics.
Keywords: Drug utilization; Indicators; OPD; Prescriptions